KINERJA DA’I NAGARI DALAM MENINGKATKAN KEHIDUPAN BERAGAMA MASYARAKAT ISLAM DI KABUPATEN PASAMAN BARAT - Yudistira, Fernando; Sarwan, Sarwan; Bukhari, Bukhari (Universitas Islam Negeri Raden Intan Lampung, 2020)
The West Pasaman Regency government hopes that Da’i Nagari can improve the religious life of the Muslim community in order to achieve the vision and mission. The objectives of this study are as follows: (1) to reveal the performance process of Da’i Nagari; (2) reveal the role of Da’i Nagari; (3) reveal the evaluation of Da’i Nagari; and (4) reveal the inhibiting factors of Da’i Nagari in improving the religious life of the Muslim community in West Pasaman Regency. The research subjects consisted of 6 Da’i Nagari people. Each nagari was taken by 2 Da’i Nagari who served in Nagari Koto Baru, Kapa and Lingkuang Aua. The 3 nagari are inhabited by Javanese, Minang and Batak (JAMBAK) tribes. Data were collected through observation, interviews and documentation. The results of this study indicate, the process of improving the religious life of the Muslim community in West Pasaman Regency is related to how Da’i Nagari’s efforts to empower the community through religious programs. The materials given by Da’i Nagari to the community were selected according to the conditions of the people in West Pasaman Regency. Empowerment as a learning process is carried out by Da’i Nagari by teaching children in TPA. Da’i’s efforts to empower the community through religious programs such as sermons, lectures, TPA education, TPA guidance, and so on. Da’i Nagari also acts as a facilitator, educator, messenger and skills. Evaluation of the improvement of the religious life of the Muslim community is carried out by making comparisons between the data and facts obtained in the field, then reported to the nagari then the nagari party provides a report to the sub-district and to the welfare area. This report aims to assess the extent to which the activity process has been carried out. The inhibiting factor is the fanaticism of the community towards one mazhab and the availability of a limited budget and the lack of community participation in accepting the empowerment carried out by Da’i Nagari.